The Importance of Building Effective Communication Between the Leader and the Members of the Organization - Ramadina, Rifda; Rahayu, Putri; Akmalia, Rizki; Lativah, Hafni; Nasution, Hafiz Yusuf; Batubara, Rahmad Riadi (Peneliti.net, 2023)
Effective communication is the process of exchanging ideas, thoughts, and information in a way that best suits goals and objectives. Simply put, it is nothing more than an expression of the sender's point of view in a way that is most easily understood by the recipient. Communication is one of the most important things that must be understood by all members of the organization. It is hoped that understanding communication can be the first step in building harmonious relationships within an organization. The purposes of communication in organizations include providing information, feedback, controlling, influencing, problem solving, decision making, encouraging change, and forming groups. This journal discusses the importance of building effective communication between the chairman and members in an organization. This journal uses a literature study research approach. Research using literature studies is research by analyzing a number of journals and articles from relevant previous research. Data collection was carried out through online research by searching for journals and articles via Google Scholar. Then it is rearranged into a complete journal that discusses the topic chosen to be developed.